Engaging school students for enabling water security: Systemic challenges and search for opportunities - Shivany, S.; Coonghe, P.A.D.; Srikantha, S.; Karthiga, I.; Dishalini, V. (University of Jaffna, Sri Lanka, 2022)
Student engagement is one of the key means to enhance water security in developing countries where water crisis is a prominent issue for the development of the regions. In terms of water security, educational and policy interventions at the school system level can drive the goals of water security and sustainability in water usage. The multifaceted relationship among education system, water pollution, waste management and environmental squalor requires multiple initiatives for ensuring water security in the Northern Province (NP) of Sri Lanka. As a step towards making NP secure for cleaner water consumption, a community-based action research project was set to foster the development of a model for engaging students whom in turn would enable water security. The present study attempted to analyze the opportunities and systemic challenges in engaging school students for water security in the NP of Sri Lanka. The data for this study were collected through systematic interactions using the World Café as a method for discussion with selected stakeholders of the educational sectors in the three divisions of the NP: Nallur, Kopay and Akkarayan. Thematic analysis of workshop records was the primary method used. This revealed that following four themes had been important to workshop participants: water in the curriculum, awareness programs, water administration, and student stewardship in the school system. From the perspective of the school stakeholders in the system, school curriculum shall be designed with creative works for enabling water security, awareness lessons for students to learn the pros and cons of the existing school water supply system, and the students’ own individual responsibilities. Other findings from analysis of the data indicated that participants expressing that awareness should be given to all categories of people on sustainable consumption, effective irrigation methods, and the importance of planting trees. The third important theme identified in this action research was water administration, which they argued should be integrated with waste disposal and wastewater management at schools, motivation for sustainable consumption via effective monitoring and evaluation processes, rainwater harvesting, and involvement in research related to water security. The fourth theme identified was to enable water security through engaging students via some form of students, stewardship. This study identified lack of integrated participation of all water stakeholders with the school system, inefficient water resource management, unbefitting approaches existing in the system, unsuitable policy making, lack of awareness about the findings derived by researchers in the school water system, and lack of motivation for individual leaders who work towards water security, are also the contributing factors. From the school stakeholders’ point of view, negative attitudes towards school-level participation, academic work overload, exam- oriented education system and current economic crisis are main challenges for engaging students; however it was exposed that there are opportunities as the WASPAR’s (Water Security through Participatory Action Research project) initiatives motivate many people in the school system to engage in water security. The intellectuals with experience and exposure are interested to engage in water security with the university community through collaborative research work and engaging students via student, stewardship program.
Keywords: Water security; Water stakeholders; School students; World café discussions; Northern Province; Sri Lanka